Avaliação da tomografia de coerência óptica em pacientes portadores de degeneração macular relacionada à idade tratada com terapia fotodinâmica com verteporfina - Bordon, Arnaldo Furman [UNIFESP] (2008)
PURPOSE: To identify the optical coherence tomography (OCT) findings in patients with age-related macular degeneration (ARMD) treated with photodynamic therapy (PDT). STUDY DESIGN: Open, non-randomized, interventional case series. METHODS: ARMD patients were submitted to a complete ophthalmological examination, fluorescein angiography, and OCT at baseline (V0), 3, 6, 9 and 12 months (V3, V6, V9 and V12, respectively). PDT was carried out according to the TAP study. Visual acuity (VA) was measured using the logMAR ETDRS chart. The following foveal measurements were performed: foveal intraretinal thickness (FIRT), foveal choriocapillaris - RPE complex thickness (FCC-RPET) and total foveal thickness (TFT). The extrafoveal thicknesses measured were: extrafoveal intraretinal thickness (EFIRT), extrafoveal choriocapillaris - RPE complex thickness (EFCC-RPET) and total extrafoveal thickness (TEFT). Statistical analysis was performed using the block variance analysis test. RESULTS: Twenty-three eyes of 23 patients were enrolled. This study identified nine OCT patterns: 1) thickening of the foveal intraretinal layers; 2) thickening of the extrafoveal intraretinal layers; 3) thickening of the foveal choriocapillaris - RPE complex; 4) thickening of the extrafoveal choriocapillaris - RPE complex; 5) intraretinal fluid; 6) subretinal fluid; 7) subretinal pigment epithelium (RPE) fluid; 8) vitreo-retinal adhesion; 9) foveal depression. At baseline, FIRT and TFT were 398.5 µ and 639.2 µ, respectively. At V12 they were 173.7 µ e 423.9 µ, respectively, and this change was statistical significant (p=0.008 e p=0.003, respectively). The variation of the other foveal and extrafoveal measurements were not statistically significant. Foveal depression was present at baseline in 36.4% of the eyes, whereas at V12 it was present in 78.3%. Subretinal fluid was present in 36.4% of eyes at V0 and in 8.7% at V12. VA at baseline was 0.93 and it V12 was 1.04 (p=0,127). CONCLUSIONS: Visual acuity was stable throughout the study. Foveal depression was reestablished in 78.3% at V12. FIRT and TFT decreased at a statistical significant level, from V0 to V12.